Physiology - Costanzo, Linda S. (Philadelphia, Pennsylvania : Williams & Wilkins, 1995)
Clear, consistent, and user-friendly, this edition of Physiology, by renowned physiology instructor Dr. Linda Costanzo, offers a comprehensive overview of core physiologic concepts at the organ system and cellular levels. It presents information in a short, simple, and focused manner, making it an ideal combination textbook and review guide for the USMLE Step 1. You'll grasp all the essential and relevant physiology knowledge you need for absolute success in school and on your exams!
1. Cell Physiology -- 2. Neurophysiology -- 3. Cardiovascular Physiology -- 4. Respiratory Physiology -- 5. Renal and Acid-Base Physiology -- 6. Gastrointestinal Physiology -- 7. Endocrine Physiology -- Comprehensive Examination -- Index.
Includes index.
Keywords: PHYSIOLOGY